From boom to bust? A critical look at US shale gas projections - Philipp M. Richter (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
US shale gas production is generally expected to continue its fast rise. However, a cautious evaluation is needed. Shale gas resource estimates are potentially overoptimistic and it is uncertain to which extent they can be produced economically. Moreover, the adverse environmental effects of ever more wells to be drilled may lead to a fall in public acceptance and a strengthening of regulation. The objective of this paper is hence twofold: providing a critical look at current US shale gas projections, and investigating in a second step the implications of a less optimistic development by means of numerical simulation. In a world of declining US shale gas production after 2015, natural gas consumption outside the USA is reduced from its reference path by at least as much as US consumption. Trade flows are redirected, and the current US debate on LNG export capacity requirements becomes obsolete.
Keywords: Q37; L71; Q41; Q33; C61; Q53; 330; Natural Gas; Shale; USA; Scenarios; Equilibrium Modeling